Elastic and Deformation Characteristics of MSWI Bottom Ash for Road Construction - Phan, V. T.; Nguyen, T. T. H. (Engineering, Technology & Applied Science Research, 2020)
Bottom ash from Municipal Solid Waste Incineration (MSWI) is a typical granular material resulting from the incineration of domestic waste. It is mainly used in road engineering substituting traditional natural aggregates. As the characterization of the mechanical behavior is essential, the work presented in this paper pursues the study of the elastic and deformation characteristics of bottom ash, in particular Young’s modulus and Poisson’s ratio. From the consolidated-drained triaxial test data, it was possible to extract fundamental material parameters about the samples, including their Young’s modulus E0.2 and E50, its Poisson’s ratio ν, and its maximum deviatoric stress peak. These parameters were then used in computer models to predict how the bottom ash will behave in a larger-scale engineering application. Furthermore, the mechanical behavior of bottom ash related to road construction’s loading condition, especially the secant modulus, was detailed.